Synthesis and Biological Activity Evaluation of 2-Cyanopyrrole Derivatives as Potential Tyrosinase Inhibitors - Hu, Ya-Guang; Gao, Zhu-Peng; Zheng, Ying-Ying; Hu, Chun-Mei; Lin, Jing; Wu, Xiao-Zheng; Zhang, Xin; Zhou, Yong-Sheng; Xiong, Zhuang; Zhu, Dao-Yong (Frontiers in Chemistry, 2022)
Tyrosinase, a key enzyme in melanin biosynthesis, plays important role in the browning of foods as well as in melanin deposition related diseases. In order to find potential inhibitors of tyrosinase, two series of pyrrole derivatives A (1 ~ 17) and B (1 ~ 8) were synthesized and screened for their inhibitory activities on tyrosinase. Most of 2-cyanopyrrole derivatives exhibited effective inhibitory activities. Especially, A12 exhibited the strongest inhibitory activities, with the IC50 values of 0.97 μM, which is ~ 30 times stronger than the reference inhibitor Kojic acid (IC50: 28.72 μM). The inhibitory mechanism analysis results revealed that A12 was a reversible and mixed-type inhibitor. Molecular docking experiments clarified the interaction between A12 with tyrosinase. Furthermore, A12 (100 μM) presented effective inhibitory on tyrosinase in B16 melanoma cells with inhibition of 33.48%, which was equivalent with that of Kojic acid (39.81%). Accordingly, compound A12 may serve as the lead structure for further design of potent tyrosinase inhibitors.